The effects of variable viscosity on magnetic field intensity with heat, mass transfer over a vertical plate - Abubakar, Hamza; Isah, Sani; Uwanta, I. J. (Vietnam Journal of Science and Technology, 2022)
This paper examines the effects of variable viscosity with heat and mass transfer over a vertical layer on the magnetic field intensity. The governing equation of continuity, energy, momentum, and concentration is transformed into the ordinary differential equations and then solved through the technique of perturbation. Expressions were generated for distribution of velocity, temperature, and concentration. Tests for parameter values of importance are described graphically and addressed quantitatively from a practical point of view.